PENGEMBANGAN MEDIA AUDIOVISUAL BERBENTUK ANIMASI UNTUK MENINGKATKAN KETERAMPILAN MENGANALISIS INFORMASI SISWA KELAS V SD TUNAS PELITA BINJAI - Ajeng Sestya Ningrum; Wisman Hadi; Daulat Saragih (UIN Sumatera Utara Medan, 2022)
The purpose of this research is to develop audiovisual tools in the form of animation to improve the skills to analyze information of students Category V SD Tunas Pelita Binjai. This research is motivated by the lack of audiovisual media applications in elementary schools and teachers less improve audiovisual media. The formulation of the problem in this research is: a) How to develop audiovisual Media in the form of animation on the“ theme of 7 events in life and subtheme (2) national events of the colonialism Era?”. b) How is the feasibility of audiovisual Media in the form of animation to improve students ' information analysis skills on“ theme 7 events in life and subtheme (2) national events of the colonialism Era?”. c) How is the effectiveness of audiovisual media in improving students ' information analysis skills on“ theme 7 events in life and subtheme (2) national events of the colonialism Era”. This research was conducted in SD Tunas Pelita Binjai with the number of participants is 30 students of fifth grade. The procedure for this research is development (research and development). The results of this research is to show that the way the development of audiovisual Media in the form of animation on the